2020
DOI: 10.1101/2020.09.03.20183947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2-specific IgA and limited inflammatory cytokines are present in the stool of select patients with acute COVID-19

Abstract: Background and aims: Immune dysregulation caused by SARS-CoV-2 infection is thought to play a pathogenic role in COVID-19. SARS-CoV-2 can infect a variety of host cells, including intestinal epithelial cells. We sought to characterize the role of the gastrointestinal immune system in the pathogenesis of the inflammatory response associated with COVID-19. Methods: We measured cytokines, inflammatory markers, viral RNA, microbiome composition and antibody responses in stool and serum samples from a prospective… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 59 publications
2
47
0
2
Order By: Relevance
“…This study raises the premise that the cytokine storm observed in COVID-19 cases might be correlated with disease severity, as IL-2, IL-7, IL-10, G-CSF, MCP-1, IP-10, TNF-α, and MIP-1α levels were higher in ICU patients compared with non-ICU ones [ 63 ]. Moreover, a study evaluating a cohort of 44 hospitalized COVID-19 patients reported the existence of higher median fecal levels of IL-8 and lower levels of fecal IL-10 in COVID-19 patients compared with control individuals [ 65 ]. Furthermore, IL-23 fecal levels were increased in severe patients, suggesting the involvement of the GI tract in the SARS-CoV-2 infection in an immunological manner [ 65 ].…”
Section: What Is the Evidence So Far That Links Gut Microbiota Commentioning
confidence: 99%
See 4 more Smart Citations
“…This study raises the premise that the cytokine storm observed in COVID-19 cases might be correlated with disease severity, as IL-2, IL-7, IL-10, G-CSF, MCP-1, IP-10, TNF-α, and MIP-1α levels were higher in ICU patients compared with non-ICU ones [ 63 ]. Moreover, a study evaluating a cohort of 44 hospitalized COVID-19 patients reported the existence of higher median fecal levels of IL-8 and lower levels of fecal IL-10 in COVID-19 patients compared with control individuals [ 65 ]. Furthermore, IL-23 fecal levels were increased in severe patients, suggesting the involvement of the GI tract in the SARS-CoV-2 infection in an immunological manner [ 65 ].…”
Section: What Is the Evidence So Far That Links Gut Microbiota Commentioning
confidence: 99%
“…Moreover, a study evaluating a cohort of 44 hospitalized COVID-19 patients reported the existence of higher median fecal levels of IL-8 and lower levels of fecal IL-10 in COVID-19 patients compared with control individuals [ 65 ]. Furthermore, IL-23 fecal levels were increased in severe patients, suggesting the involvement of the GI tract in the SARS-CoV-2 infection in an immunological manner [ 65 ]. More severe cases were also associated with higher serum levels of IL-6, IL-8, tumor necrosis factor α (TNF-α), C-reactive protein (CRP), lactate dehydrogenase (LDH), D-dimer, ferritin, and procalcitonin [ 65 ].…”
Section: What Is the Evidence So Far That Links Gut Microbiota Commentioning
confidence: 99%
See 3 more Smart Citations